Software for storage and processing coded messages for the international exchange of meteorological information; Journal of Physics: Conference Series; Vol. 803 : Information Technologies in Business and Industry (ITBI2016) - Popov V. N. Vladimir Nikolaevich (2017, 2017)
Title screen